Use of Drugs and Treatment Cost in Acute Watery Diarrhoea of Under-2 Children Attending a Tertiary Hospital of Bogra - Muraduzzaman, AKM; Islam, S M Rashed-Ul; Siddiqui, Md. Mahmudur Rahman (Journal of Medicine, 2014)
A cross-sectional study was conducted in Mohammad Ali hospital (MAH) of Bogra from Bangladesh to evaluate the hand washing and exclusive breast feeding (EBF) practice and to explore the rational use of anti-diarrhoeal therapy in Acute Watery Diarrhea (AWD) and expenditure of the family in treatment. A total of 660 under-2 children attending at MAH with the complaints of AWD were selected for the study. The mean age (mean±SD) of the attended child was 11.75±5.16 months. About 80% of the respondents (mothers of under-2 child) were below SSC level in terms of educational status while about 9% were illiterate. About 85% of the respondent seek treatment from non-registered practitioners (NRP) while registered doctors contributed only among 12% which was found statistically significant in comparison to their family income (p<0.001). Azythromycin was the most prescribed drugs (22.4%) followed by ciprofloxacin (21.7%) and erythromycin (15.9%) which was mostly prescribed by non-registered doctors (p <0.05). The families had to spend a mean cost of Tk. 209/- which was spend significantly high on NRP (p<0.05) as a direct treatment cost. Misuse of antibiotics was observed from NRP and a handsome amount was spending on them. Moreover, About 91% of the total respondent did not practice exclusive breast feeding and about 99% mother found to admit improper hand hygiene. To reduce unnecessary expenditure and ensure proper treatment of AWD, it was recommended to aware the community on quality management at government facility. DOI: http://dx.doi.org/10.3329/jom.v14i2.19665 J Medicine 2013, 14(2): 143-148